Inflammatory myofibroblastic tumour of the conjunctiva masquerading as ocular surface squamous neoplasia. Issue 2 (March 2022) - Singh, Manpreet; Saini, Manu; Chatterjee, Debajyoti; Mehta, Aditi; Kaur, Manpreet; Gupta, Pankaj
A 63-year-male had painless, progressive, yellowish-pink, immobile conjunctival mass with prominent feeder vessels in the right eye of 1-year duration. The rest of the ophthalmic examination was unremarkable. MRI showed no extension into orbit or extraocular muscles. An excision biopsy with the amniotic membrane patch was performed. Histopathology confirmed inflammatory myofibroblastic tumour (IMT) with SMA and calponin positivity on immunohistochemistry. Complete surgical excision, amniotic membrane, and oral steroids provided long-term relief from recurrence. The conjunctiva is a rare site for IMT, and IMT should be kept in the differentials for atypical cases of ocular surface neoplasia.